2011
DOI: 10.5402/2011/925316
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management, and Outcome of Molar Pregnancies at a Tertiary Care Hospital in Quetta, Pakistan

Abstract: Molar pregnancies represent a significant burden of disease on the spectrum of gestational trophoblastic diseases. The incidence appears to be higher in women from South Asia. The purpose of our prospective study was to determine the incidence, presentation, and outcomes of all molar pregnancies at our institution. During the study period, there were a total of 16,625 patients admitted to our department; out of whom 85 patients were diagnosed with a molar pregnancy. Vaginal bleeding was the commonest symptom (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 8 publications
5
21
2
4
Order By: Relevance
“…5 However, Fatima et al, noted bleeding per vaginum to be the commonest symptom seen in as many as 94.2%. 14 One of the most classical symptom i.e. passage of grape like vesicles per vaginum was seen in only 9.1% of patients in the present study; while in the Nigerian study by Ocheke AN et al, it was found in 60% cases.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…5 However, Fatima et al, noted bleeding per vaginum to be the commonest symptom seen in as many as 94.2%. 14 One of the most classical symptom i.e. passage of grape like vesicles per vaginum was seen in only 9.1% of patients in the present study; while in the Nigerian study by Ocheke AN et al, it was found in 60% cases.…”
Section: Discussioncontrasting
confidence: 64%
“…Age less than 20 years is not considered as a risk factor by WHO, though some experts have observed both extremes (<20 years and >35 years) to be at increased risk of disease. [12][13][14][15] In the present study the commonest symptom after amenorrhea is per vaginum bleeding, seen in 68.2% of patients. The clinical study from Dubai reported incidence of vaginal bleeding in 29% patients only.…”
Section: Discussionsupporting
confidence: 52%
“…Mean age of GTD cases was 25.09±7.9 years (Range:15-50 years). Among 102 cases of GTD, range of parity was from 0 to 11 which was comparable (0 to 17) to a study by Fatima et al 10 In this study, most of the GTD cases presented as P/V bleeding (67.6%) which is similar to studies conducted by Fatima et al 10 and Hou et al 11 USG diagnosed cases of GTN in 29.4% and more than half of these,17/30 (56.6%) were diagnosed in first trimester, reflecting the diagnosis of disease by USG in early pregnancy. 12 The risk of GTN for complete HM (15-20%) is significantly higher than for partial HM (0.2-4%) [13][14][15][16] as was also noted in this study CHM (15.5%) and PHM (5.5%).…”
Section: Discussionsupporting
confidence: 55%
“…Asian women are at higher risk of developing hydatidiform mole. The incidence of hydatidiform mole in Southeast Asia is approximate 0.5 % [ 12 ], which is significantly higher than that in the United States and the United Kingdom. Interestingly, Caucasians have higher incidence of hydatidiform mole than African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of ectopic pregnancy has not changed substantially in the United States since the early 1990s [ 7 , 8 ], other studies showed that the incidence of ectopic pregnancy has increased during the 1980s and 1990s in developed countries including the United Kingdom [ 4 , 9 , 10 ]. The incidence of hydatidiform mole is lower in the United States (1 in 1000 pregnancy), but it is much higher in Asia, up to 1 in 100 pregnancy in Indonesia as well Pakistan [ 11 , 12 ]. One study has also indicated that incidence of hydatidiform mole is increased from 1 in 611 viable conceptions in 1997 to 1 in 528 viable conceptions in 2008 in United Kingdom [ 13 ].…”
Section: Introductionmentioning
confidence: 99%